2017
DOI: 10.1007/s00259-017-3879-x
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-man PET study of [18F]PSS232, a fluorinated ABP688 derivative for imaging metabotropic glutamate receptor subtype 5

Abstract: Brain uptake of [F]PSS232 matched the distribution of mGlu and followed a two-tissue compartment model. The well-defined kinetics and the possibility to use reference tissue models, obviating the need for arterial blood sampling, make [F]PSS232 a promising fluorine-18 labeled radioligand for measuring mGlu density in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…mGluR5 availability was quantified with the novel PET radioligand [ 18 F]PSS232 which is a non-competitive selective antagonist of mGluR5 (Sephton et al, 2014;Warnock et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…mGluR5 availability was quantified with the novel PET radioligand [ 18 F]PSS232 which is a non-competitive selective antagonist of mGluR5 (Sephton et al, 2014;Warnock et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…To quantify sleep-wake associated changes in the availability of mGluR5 that may occur simultaneously with the above described local changes in Glu, GLX and GABA, the newly developed, highly selective, non-competitive mGluR5 antagonist for PET brain imaging, [ 18 F]PSS232, was employed (Sephton et al, 2014;Warnock et al, 2018).…”
Section: Whole-brain Mglur5 Availability Is Elevated After Sleep Deprmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo studies with [ 18 F]PSS232 in rats showed rapid kinetics favorable for evaluation within 70-min PET recordings, despite the presence of some displaceable binding in the cerebellum reference region. The first [ 18 F]PSS232 ( 83 ) study in humans showed well-behaved cerebral kinetics relative to the arterial input function, which was stably quantifiable with dynamic recordings lasting only 45 min [ 204 ]. The considerable metabolic stability of the tracer, which remained 60% intact in plasma samples collected at 90 min after injection, presents a distinct advantage for PET studies with this tracer.…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…PET allows generating well-defined tissue radioactivity concentration time curves ( C ( t )) from image data. In addition, blood can be sampled to measure the blood C ( t ) simultaneously [ 13 , 14 ]. PET kinetic modelling is a standard method for the quantification of brain function, for example, glucose consumption or neuroreceptor density in preclinical and clinical imaging [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%